Engineered nano-foam of tri-metallic (FeCuCo) oxide catalyst for enhanced hydrogen generation via NaBH4 hydrolysis. (October 2021) - Patil, Komal N.; Prasad, Divya; Bhagyashree,; Manoorkar, Vilas K.; Nabgan, Walid; Nagaraja, Bhari Mallanna; Jadhav, Arvind H.
Abstract: Catalytic hydrolysis of sodium borohydride can potentially be considered as a convenient and safe method to generate hydrogen, an environmentally clean and sustainable fuel for the future. The present effort establishes the development of FeCuCo tri-metallic oxide catalyst by a simple, single-step solution combustion synthesis (SCS) method for hydrogen generation from NaBH4 hydrolysis. Amongst series of FeCuCo tri-metallic oxide catalyst synthesized, FeCuCo with 50:37.5:12.5 wt% respective precursor loading displayed remarkable activity by generating hydrogen at the rate of 1380 mL min −1 g −1 (1242 mL in 18 min) with turnover frequency (TOF) of 62.02 mol g −1 min −1 . The catalyst was characterized by using various techniques to understand their physiochemical and morphological properties. The results revealed that the catalyst synthesized by combustion method led to the formation of FeCuCo with appreciable surface area, porous foam-like morphology and high surface acidity. Major factors affecting the hydrolysis of NaBH4 such as catalyst loading, NaOH concentration and temperature variation were studied in detail. Additionally, the FeCuCo catalyst also displayed substantial recyclability performance up to eight cycles without considerable loss in its catalytic activity. Therefore, FeCuCo oxide can be demonstrated as one of the most efficient, cost effective tri-metallic catalyst so far for application in the hydrogen generation. Graphical abstract: Image 1 Highlights: Solution combustion synthesis is a one-step, low-temperature method. Nano-form like FeCuCo tri-metallic oxide catalyst was obtained from SCS method. Dense porous network and surface acidic sites were typical features of the catalyst. The catalyst produced hydrogen at the rate of 1380 mL min −1 g −1 from NaBH4 hydrolysis. The catalyst could be recycled competently up to eight recycles.